SIGNIFICANCE OF HISTOPATHOLOGICAL PARAMETERS IN FEMALE PATIENTS AFTER PLACEMENT OF BREAST IMPLANTS - Lilić, Nemanja; Lelas, Vanja; Lazarevic, Tara; Kovacevic, Dijana; Kotur, Milica (Medicinski podmladak, 2025)
Introduction: Mammoplasty is a surgical procedure of placement of breast implants for aestetic reasons or because of breast reconstruction after mastectomy after cancer. As the implant represents a foreign body, there is an inflammatory reaction and complications (most often capsule contractures, most rarely anaplastic large cell lymphoma), with different histopathological presentations (synovial metaplasia, chronic inflammation, dystrophic calcifications, granulomas around a foreign body type). Clinically, these complications are presented as tumor-like changes.Aim: Aim of the paper is to show the most significant histopathological parameters, age of the patients at the time of the complications, period that passed from the placement of the implant to the onset of complications and the existence of previous cancer. Material and methods: This study included patients with breast implants in the period of January 2019 to December 2023. Evaluating data from medical records, we performed a retrospective study, which included: age of the patient at the time of complications, reasons for performing mammoplasty, period that passed from mammoplasty to the appearance of complications. Archived material was used (paraffin molds and histopathological material stained with the hematoxylin-eosin method, as well as immunochistochemical stainings). Descriptive statistics methods (Fishers exact probability test) were used for data analysis.Results: Average age of the patients was 50.1 years, and the period that passed from the placement of the implant to the appearence of complications was 16.7 years. The breast cancer previously had 22%. Most common histopathological parameters were synovial metaplasia (100%) followed by chronic inflammation (76%), foreign material (52%) and granuloma around a foreign body (32%). The breast surgery was performed for cosmetic reasons in 88% of the patients.Conclusion: This study proved that the patients were older and that more time passed before complications occurred than was shown in literature. Large percent of patients had the procedure only because of cosmetic reasons.
Keywords: breats implant, breast cancer, complications, synovial metaplasia, chronic inflammation